2003
DOI: 10.1096/fj.02-1203fje
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of autoantibodies against Nogo‐A and MOG in the absence of an encephalitogenic T cell response: implication for immunotherapeutic approaches in neurological diseases

Abstract: Vaccinations against various antigens of the central nervous system (CNS) are gaining increasing interest as a therapeutic approach in a variety of neurological diseases such as spinal cord injury, ischemic stroke, Alzheimer disease, or spongiform encephalopathy. In the present work, the time window after spinal cord injury allowing potentially therapeutic antibody to penetrate the damaged blood-brain barrier (BBB) was measured by intravenous injection of a monoclonal anti-Nogo-A antibody. Although an influx o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Similarly low CSF concentration/serum concentration ratios have been observed for other peripherally administered MAbs in mice, rats, and humans (1,8,14,21,23,24). Despite encephalitis and CNS inflammation in the hamsters, only a small fraction of the peripherally administered hE16 efficiently crosses the bloodbrain barrier and inhibits and/or controls infection.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly low CSF concentration/serum concentration ratios have been observed for other peripherally administered MAbs in mice, rats, and humans (1,8,14,21,23,24). Despite encephalitis and CNS inflammation in the hamsters, only a small fraction of the peripherally administered hE16 efficiently crosses the bloodbrain barrier and inhibits and/or controls infection.…”
Section: Discussionmentioning
confidence: 67%
“…Intrathecal or intraventricular delivery, therefore, seems an excellent system for the application of therapeutic antibodies to the CNS. In contrast, earlier studies showed that circulating systemic antibodies against Nogo-A penetrated very poorly into the CNS due to a rapid resealing of the blood -brain barrier (Merkler et al, 2003).…”
Section: Discussionmentioning
confidence: 73%
“…It was shown that elevated levels of the autoantibody catalytic activity correlated with an autoimmune response in human and mice models (16,21,35). Moreover, data from several laboratories indicate that autoantibodies can readily penetrate the blood-brain barrier (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%